How artificial intelligence shapes the future of biomaterials? - Masoud Mozafari (Next Materials)
Biomaterials are playing a transformative role in modern medicine, revolutionizing both diagnosis and treatment options. The advent of advanced artificial intelligence (AI) tools is poised to significantly impact the field of biomaterials. AI is expected to play a critical role not only in the design and development of biomaterials but also in establishing new standards and refining definitions within this domain. AI can provide invaluable assistance by offering sophisticated tools to organize and analyze vast amounts of data. By leveraging AI’s capabilities, researchers can efficiently sift through extensive datasets, interpret results, and verify the efficacy of new biomaterials across a wide range of applications. This data-driven approach facilitates a deeper understanding of biomaterial interactions and performance, ensuring that new innovations meet rigorous standards. In this era, refining definitions and establishing a universal understanding are crucial for evaluating biomaterials more efficiently. AI can help achieve this by identifying patterns and correlations that might be overlooked by traditional methods, leading to more precise and reliable criteria for biomaterial assessment. Looking ahead, the integration of comprehensive data and advanced AI tools is expected to significantly enhance the effectiveness and quality of biomaterials. This synergy will ensure that biomaterials can meet the diverse and evolving needs of modern medicine, driving forward innovations that improve patient outcomes and healthcare practices.